2019
DOI: 10.3390/brainsci9100270
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cell-Based Therapies for Traumatic Brain Injuries

Abstract: Traumatic brain injuries (TBIs) are a leading cause of death and disability. Additionally, growing evidence suggests a link between TBI-induced neuroinflammation and neurodegenerative disorders. Treatments for TBI patients are limited, largely focused on rehabilitation therapy, and ultimately, fail to provide long-term neuroprotective or neurorestorative benefits. Because of the prevalence of TBI and lack of viable treatments, new therapies are needed which can promote neurological recovery. Cell-based treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…One of the important and common complications of TBI is also anxiety, which constitutes a signi cant part of the long-term symptoms and complications of TBI [49]. In the present study, post-traumatic anxiety-like behavior was indicated by a decrease in time In line of our results of memory, administration of mouse neural stem / progenitor cells (NSPCs) to mice with TBI could improve memory [51], whereas human NSPC, regardless of its positive e cacy and relieving motor de cits, had no effect on the development of long-term cognitive activity and memory [52]. In a study conducted by Zhou et al (2019), it was shown that MSCs administration ameliorated neurological dysfunction and also memory and learning impairment after TBI [53].…”
Section: Discussionsupporting
confidence: 75%
“…One of the important and common complications of TBI is also anxiety, which constitutes a signi cant part of the long-term symptoms and complications of TBI [49]. In the present study, post-traumatic anxiety-like behavior was indicated by a decrease in time In line of our results of memory, administration of mouse neural stem / progenitor cells (NSPCs) to mice with TBI could improve memory [51], whereas human NSPC, regardless of its positive e cacy and relieving motor de cits, had no effect on the development of long-term cognitive activity and memory [52]. In a study conducted by Zhou et al (2019), it was shown that MSCs administration ameliorated neurological dysfunction and also memory and learning impairment after TBI [53].…”
Section: Discussionsupporting
confidence: 75%
“…Preclinical works using NSCs in TBI rat models showed that human NSCs (hNSCs) are capable of surviving engraftment and differentiating into neurons which, in turn, correlate with improvements in neurological recovery [19,60]. Transplanted NSCs can survive in the traumatically injured brain, differentiate into neurons and/or glia, and attenuate motor dysfunction after TBI [61].…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…In addition to promoting angiogenesis, BM-MSCs have been shown to ameliorate neuronal dysfunction induced by TBI through promotion of survival and normal growth of surviving neurons. Although neuronal cell death is a major contributor to poor neurologic outcome post-TBI, TBI not only induces cell death in immature granular neurons, it also causes significant dendritic and synaptic degeneration [60]. These observations point to a potential anatomic substrate to explain, in part, the development of post-traumatic memory deficits [135].…”
Section: Bone Marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Stem cell-based therapies to treat neuroinflammation in both the acute and chronic phase of TBIs is an approach that has the potential to mitigate secondary cell loss and to promote neurological and functional recovery. Several very recent reviews document the testing, use, and efficacy of pharmacological and stem cell replacement therapies both separately and in combination [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Here, our review serves to highlight some of the most recent research reports in the use of stem cell therapies alone to treat the destructive and chronic neuroinflammatory processes of TBIs.…”
Section: Neuroprotection—stem Cell Therapies Targeting Neuroinflammentioning
confidence: 99%
“…Recently published reviews have documented the use and efficacy of stem cell replacement therapies, pharmacological treatments, and combination therapies in the preclinical and basic research settings to treat TBIs [ 8 , 9 , 10 , 11 , 12 , 13 ]. This current review, however, is intended as a perspective focusing on the three therapeutic points mentioned through selected and recent preclinical and basic research in the efficacy of combinatorial stem cell therapies used to treat TBIs.…”
Section: Introductionmentioning
confidence: 99%